Navigating accent bias in German: children's social preferences for a second-language accent over a first-language regional accent - Hanulíková, Adriana (Frontiers in Language Sciences, 2024)
Spoken language conveys rich sociolinguistic information about a speaker's language background. Previous research indicates that both monolingual and bilingual children use this information when making social decisions. They prefer local speakers whose accent or variety matches their own over speakers of foreign languages or second-language speakers. What remains unclear is how exposure to diverse linguistic communities affects children's preferences for non-local accents. This study examines social preferences for a regional and a second-language accent as a function of prior exposure to diverse accents and languages, measured on a continuous scale. German-speaking primary-school children (aged 7-10) were asked to choose stickers in a forced-choice task using animated cartoon characters. We replicated the observed social preferences for one's local accent. Interestingly, when the local accent was absent, children socially preferred a second-language accent (American) over a first-language regional accent (Bavarian), even though both accents were equally intelligible and relatively unfamiliar to the children, as determined through a sentence repetition task and a geographical classification task. Children's choices were not explained by continuous measures of accent or bilingual exposure. The results suggest a complex interaction of various factors not limited to the speakers' first-or second-language status.